2015
DOI: 10.1371/journal.pone.0136774
|View full text |Cite
|
Sign up to set email alerts
|

Mouse CD11b+Kupffer Cells Recruited from Bone Marrow Accelerate Liver Regeneration after Partial Hepatectomy

Abstract: TNF and Fas/FasL are vital components, not only in hepatocyte injury, but are also required for hepatocyte regeneration. Liver F4/80+Kupffer cells are classified into two subsets; resident radio-resistant CD68+cells with phagocytic and bactericidal activity, and recruited radio-sensitive CD11b+cells with cytokine-producing capacity. The aim of this study was to investigate the role of these Kupffer cells in the liver regeneration after partial hepatectomy (PHx) in mice. The proportion of Kupffer cell subsets i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 49 publications
2
54
0
1
Order By: Relevance
“…The TNF produced by the midzone macrophages may have been consumed by the surrounding hepatocytes in order to protect against hepatocyte injury and prevent TNF spillover into the circulation. TNF is known to be either hepatotoxic or hepa- toprotective, depending on the condition of the liver [30,31] . Consistently, TNF in the liver of LPS-tolerant mice may enhance the reactivity of CRP production to E. coli challenge (online suppl.…”
Section: Cd68mentioning
confidence: 99%
“…The TNF produced by the midzone macrophages may have been consumed by the surrounding hepatocytes in order to protect against hepatocyte injury and prevent TNF spillover into the circulation. TNF is known to be either hepatotoxic or hepa- toprotective, depending on the condition of the liver [30,31] . Consistently, TNF in the liver of LPS-tolerant mice may enhance the reactivity of CRP production to E. coli challenge (online suppl.…”
Section: Cd68mentioning
confidence: 99%
“…Recent data suggest that lung macrophages are maintained independently by self-renewal under steady-state conditions (Guilliams et al, 2013; Hashimoto et al, 2013; Hoeffel and Ginhoux, 2015; Hoeffel et al, 2015; Jakubzick et al, 2013; Perdiguero et al, 2015; Schulz et al, 2012; Suzuki et al, 2014; Yona et al, 2013). Bone marrow-derived and circulating monocytes replenish and supplement resident macrophages only after tissue macrophage depletion and during some inflammatory/regenerative states (Hashimoto et al, 2013; Yona et al, 2013), often through a mechanism involving the chemokine receptor CCR2 (Willenborg et al, 2012; Lee et al, 2015; Nishiyama et al, 2015; Ramachandran et al, 2012). Both resident and recruited macrophages are capable of proliferation at their sites of action (Davies et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Kupffer cells, the resident hepatic macrophages, play a major role in liver inflammation by releasing ROS and a variety of pro-inflammatory cytokines, which provoke HSCs activation and induce overproduction of extracellular matrix [4]. CD68, a specific KCs marker, has been widely used to monitor KCs activation during liver injury [29]. In this study, we demonstrated that MOX significantly inhibited CD68 expression in CCl 4 -treated mice.…”
Section: Discussionmentioning
confidence: 64%